Potenciais impactos da carbamilação in vitro sobre a atividade da proteína C, proteína S e antitrombina - Neves, Yasmin Sudatti das (2023)
Hemostasis is a vital process in the body that aims to maintain the balance between the procoagulant and anticoagulant systems. An imbalance in this system can cause uncontrolled bleeding or thrombotic events. For the proper functioning of this system, some anticoagulant substances play a fundamental role. Among them, Protein C, Protein S and Antithrombin stand out. Hereditary and acquired deficiencies of these proteins are associated with serious thromboembolic complications. Protein S acts as a cofactor for activated Protein C, which acts in the cleavage of factors Va and VIIIa, whereas Antithrombin inactivates mainly thrombin and factor Xa. Carbamylation is a non-enzymatic post-translational modification that involves the reaction between cyanate and amino acids and/or proteins that can lead to conformational and functional changes in proteins. Carbamylation occurs in the body mainly due to the presence of cyanate, which is a product of urea metabolism, and also through the action of the myeloperoxidase (MPO) enzyme in inflammatory processes, which converts thiocyanate into cyanate. Studies have shown that uremia and inflammation predispose to the occurrence of hemostatic abnormalities, in this context, carbamylation can affect the activity of some proteins involved in coagulation. Therefore, this study investigated the effects of in vitro carbamylation induced with potassium cyanate (KOCN) on protein C, protein S and antithrombin activity. Carbamylation was analyzed by exposing commercial coagulation controls and plasma pools to different concentrations of potassium cyanate determined by previous study (0, 150 nm, 150 μM and 150 mM) for 6 hours at 37 °C. Afterwards, the activities of protein C, protein S and antithrombin were evaluated in controls. In the pool, antithrombin activity and thrombin time (TT) were evaluated. The results showed a reduction in protein activity after incubating the controls with KOCN 150 mM, the activity values for protein S, protein C and antithrombin were, respectively, 77%, 65% and 26% of the values obtained initially without carbamylation . In the pool, a reduction in antithrombin activity was also observed, the result was approximately 28% of the value initially obtained without KOCN, similar to the result obtained with the controls. The TT prolonged approximately 14 times when compared to the value initially obtained without incubation with KOCN. It is speculated that the underestimation of the levels of protein S, protein C and antithrombin found are occurring due to the interaction of isocyanic acid, the active form of cyanate, with proteins. TT may have reduced due to fibrinogen carbamylation. In conclusion, carbamylation of protein C, protein S, antithrombin and fibrinogen may be involved in the hemostatic abnormalities observed in uremic patients or those with inflammatory states. More studies should be carried out to examine these aspects in more detail.